Maternal knowledge, attitude and practice regarding breastfeeding in Temerloh, Pahang, Malaysia - Aye, Aye; Adul Wahab, Jantan; Tin, Myo Han; Nagis , Masroor; Taufiq Hidayat, Hasan; Shikh Farid Uddin, Akter (Academy of Family Physicians of Malaysia, 2014)

(untitled)
Background: Although, breast feeding is the best way to feed infant by providing the psychological and health benefit to mother and child, prevalence of practicing exclusive breastfeeding (EBF) for 6months and continuing it up to 2-years varies between countries and within countries from 75% in DPR Korea, Seri Lanka, Cambodia and the Solomon Islands, around half in India and less than 20% were in Thailand and Viet Nam. In Malaysia, national EBF rate in 2011 was 23.7%. Objectives: Aim of this study was to assess maternal knowledge, attitude and practices on exclusive breastfeeding and continuing it up to 2 years including its influencing factors and reasons for discontinuation of breastfeeding before 2-years. Methods: A cross sectional study was carried among 500 mothers of children aged from neonate to 3 years who attended at Maternal and Child Care Clinic, Temeloh, Pahang between July and December 2012. A face-to-face interview was done by using a semi-structured, pre-tested questionnaire including opened type questions to collect data. A cross analysis was done to infer statistical significance of influencing factors which affect pattern of breast feeding in terms of age, occupation, educational level of mother and socio-economic status of family. Results: Out of 500 mothers, 96% of them have knowledge regarding benefits of breastfeeding in general and particularly in characteristics and value of breast milk (91%), mother-infant bonding (77%). Sources of their knowledge were health personal (45.1%), media (20%), family (16.3%), and friends (14%). Regarding attitude, all mothers agreed that breast feeding is ideal food for babies, followed by agreement to feed breast milk to next child (98.6%), being comfortable with breast feeding(96%), encouraging breast feeding by family (95.8%), causing diarrhoea diseases by bottle feeding in babies (79.6), affecting on marital status by breast feeding (37%), feeling embarrassed with breast feeding (30.5), allowing breast feeding at home by employers (27%) and taking leave for breast feeding (12.6%). Regarding practices, 81% of them had early commencement of breast feeding. Exclusive breast feeding rate and continuing breastfeeding up to 2 years of age were 37.2% and 34.5% respectively. The reasons for discontinuing breastfeeding up to 2 years of age were no breast-milk production (81.7%), working mother (63.4%), refusal to feed (46.2%), retracted nipple (14%), maternal sickness (13%) and others reasons (37.6%). Mixed and bottle feeding rate were 54.4% and 22% respectively. The reasons for bottle feeding were no breast-milk production (36.4%), working mother (24.5%), refusal to feed (20%), maternal sickness (5.4%) and others (14.5%). Influence of maternal employment status on EBF was significantly (p <0.05) found out. Monthly family income was related significantly with continuing breastfeeding up to 2 years. Conclusion: EBF rate of Temerloh, Pahang was higher than that of National figure. Nevertheless, need to find out the ways to supports mothers to get higher achievement. The other reasons which influenced on discontinuing breastfeeding should be clarified in further study to get more understanding on the mothers who are unable to provide exclusive breastfeeding and continuing it up to 2 years of their children.